Application of waste from steel industry to construction material: a review - Mamdouh, Ahmed; Safiee, Nor Azizi; Hejazi, Farzad; Azarkerdar, Arash (Institute of Physics Publishing, 2019)
Concrete is material which widely used in construction projects because it has many advantages and is an inexpensive material, durable and can be molded into any shape. On the other hand, concrete has some disadvantages due to the brittle nature which made concrete also suffers from sudden failure. However, the routinely creating enthusiasm for materials by the construction business can't be totally faced by regular resources or traditional materials. Henceforth, there is a need to create elective potential materials and innovative methods to fathom the growing requests of building development. For this reason, some research introduced Slag as ecofriendly and natural materials to reinforce the concrete. Therefore, in recent years, it has concentrated on discover alternative techniques for outline, development, and support with the motivation behind delivering naturally benevolent structures. This study will present a short review on the steel slag which covered the basic chemical characteristic and also, the potential of steels slag as an alternative building material in construction. Furthermore, discussing from the manageability perspective, the recuperation of slag is certain from all viewpoints: economically, environmentally, and socially as construction material. Therefore, this paper summarizes the progresses and points out the directions for the proper use of steel slag.